LONELINESS SEBAGAI PREDIKTOR ACADEMIC BURNOUT PADA MAHASISWA PERANTAU DI UNIVERSITAS NEGERI SEMARANG - Fadlan Hilmy Rahman; Fikrotul Hanifah (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
Migrant student face unique academic and psychological challenges, particularly loneliness. Loneliness is often a hidden struggle that negatively affects academic engagement and well-being, and when prolonged, may lead to academic burnout. Academic burnout is associated with decreased academic performance, loss of motivation, increased dropout risk, and long-term mental health problems. This study aims to examine loneliness as a predictor of academic burnout among migrant students at Semarang State University. Using a quantitative approach, survey data were collected from 298 students through Google Forms, with sample size determined using G-Power analysis. Data were analyzed using simple linear regression. The results indicate that loneliness has a significant positive effect on academic burnout, explaining 27.5% of its variance (R² = 0.275). No significant differences in burnout were found based on gender or organizational involvement. These findings confirm loneliness as a significant predictor of academic burnout and contribute to the understanding of migrant students’ academic experiences in the Indonesian context.